A Simple NMR‐Based Method for Studying the Spatial Distribution of Linkers within Mixed‐Linker Metal–Organic Frameworks1. Issue 36 (15th July 2015) - Krajnc, Andraž; Kos, Tomaž; Zabukovec Logar, Nataša; Mali, Gregor
Abstract The spatial distribution of different linkers within mixed‐linker metal–organic frameworks crucially influences the properties of such materials. A simple and robust approach based on 1H spin‐diffusion magic‐angle‐spinning nuclear magnetic resonance measurements and modeling of spin‐diffusion curves is presented; this approach facilitates the distinction between homogeneous and clustered distributions. The performance of the approach is demonstrated with an example of an aluminum‐based metal–organic material DUT‐5, which has framework consisting of biphenyl and bipyridyl dicarboxylic linkers. The distribution is shown to be homogeneous in this material. The approach could be applied to studying other spatially disordered crystalline materials.